Situating Latin American Critical Epidemiology in the Anthropocene: The Case of COVID-19 Vaccines and Indigenous Collectives in Brazil and Mexico (Medicine Anthropology Theory, 2023)
Diverse histories and traditions of critical epidemiology in Latin America provide an important, although underutilised, alternative framework for engaging with the embodied health inequalities of the Anthropocene. Taking COVID-19 as ‘a paradigmatic example of an Anthropocene disease’ (O’Callaghan-Gordo and Antó 2020) and drawing on ethnographic research in Brazil and Mexico on vaccination campaigns among Indigenous Peoples, we review and analyse the scope and limits of Latin American critical epidemiology in addressing Anthropocene health. While there are intersecting and parallel dynamics between diverse national and regional histories of epidemiology, we argue that the relatively differential focus on political economy, political ecology, and colonialism/coloniality in Latin American critical epidemiology, alongside the attention to non-western disease experiences and understandings, constitute a counterpoint to biomedical and specific ‘Euro-American’ epidemiological approaches. At the same time, Indigenous understandings of health/disease processes are intimately connected with territory protection, diplomacy with non-human entities, and embodied memories of violence. We examine how this presents new and challenging questions for critical epidemiology, particularly in how the ‘social’ is defined and how to address both social justice and social difference whilst also navigating the biopolitical challenges of state intervention in the era of Anthropocene health.